2017
DOI: 10.5194/acp-2017-641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiative effects of ozone waves on the Northern Hemisphere polar vortex and its modulation by the QBO

Abstract: Abstract.The radiative effects induced by including interactive ozone, in particular, the zonally asymmetric part of the ozone field, have been shown to significantly change the temperature of the NH winter polar cap, and correspondingly the strength of the polar vortex. However, there is still a debate on whether this effect is important enough for climate simulations to justify the numerical cost of including chemistry calculations in long climate integrations. In this paper we aim to understand the 5 physic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 22 publications
5
19
0
Order By: Relevance
“…Higher values of ASO are associated with elevated geopotential height and warmer temperature over the polar lower and midstratosphere and lower geopotential heights, and colder temperatures in the tropical lower and mid-stratosphere in reanalysis data (Figures 2ab). This effect is consistent with previous work that has shown that transport controls lower stratospheric ozone concentrations (Douglass et al, 1985;Hartmann, 1981;Rood and Douglass, 1985;Hartmann and Garcia, 1979;Silverman et al, 2017).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher values of ASO are associated with elevated geopotential height and warmer temperature over the polar lower and midstratosphere and lower geopotential heights, and colder temperatures in the tropical lower and mid-stratosphere in reanalysis data (Figures 2ab). This effect is consistent with previous work that has shown that transport controls lower stratospheric ozone concentrations (Douglass et al, 1985;Hartmann, 1981;Rood and Douglass, 1985;Hartmann and Garcia, 1979;Silverman et al, 2017).…”
Section: Introductionsupporting
confidence: 93%
“…Establishing the direction of causality between stratospheric polar cap ozone and temperature/height anomalies in the CCMI is beyond the scope of this work, as daily data is needed to resolve the key processes. However previous work has suggested that dynamical transport drives ozone anomalies in the lower stratosphere (Douglass et al (1985), Hartmann (1981), Rood and Douglass (1985), Hartmann and Garcia (1979), Silverman et al (2017)).…”
Section: Discussionmentioning
confidence: 95%
“…For example, all prescribed ozone simulations show a large temperature increase in the uppermost stratosphere and mesosphere, of about 17 K above 1 hPa, below which there is significant cooling of about 0.5 K between 60 ° S and 60 ° N extending into the tropical midstratosphere (not shown). This feature in the mesosphere was described by Sassi et al (), and these high‐altitude temperature differences have also been remarked upon in studies by Gillett et al (), McCormack et al (), Peters et al (), and Silverman et al () all of which compare zonally averaged ozone in a CCM to a fully interactive configuration. Sassi et al () attribute this feature to the nonlinear addition of variations in radiative heating over diurnal cycles and bands of longitude, that acts only on the diurnal component of ZAO (this dominates the ZAO pattern in the mesosphere and tropical upper stratosphere).…”
Section: Resultssupporting
confidence: 69%
“…In the polar lower stratosphere during wintertime, zonal asymmetries in dynamics arising from waves and eddies may produce substantial zonally asymmetric features in the distribution of ozone (e.g., Hartmann, 1981). Recently, zonal asymmetries in ozone have been shown to play a substantial role in driving atmospheric circulation, independent of the zonal-mean structure of ozone in the atmosphere (e.g., Albers & Nathan, 2012;McCormack et al, 2011;Silverman et al, 2017). Additionally, a number of studies have explored the extent to which stratospheric ZAO has contributed to observed dynamical trends both in the stratosphere and at the surface, over recent decades (e.g., Crook et al, 2008;Gabriel et al, 2007;Gillett et al, 2009;Peters et al, 2015;Sassi et al, 2005;Waugh et al, 2009).…”
Section: Citationmentioning
confidence: 99%
“…However, the Atmospheric Model Intercomparison Project (AMIP)-type simulations in previous studies usually show a much less robust and less consistent EQBO minus WQBO composite in the extratropics in CCMVal2 and CMIP5 models (Butchart et al 2018;Naoe and Yoshida 2019). Causes for a poor HT relationship in CMIP5/CCMVal2 experiments might include 1) shortness of data available (Naoe and Yoshida 2019); 2) nonlinear interactions with the 11-yr solar cycle (Salby and Callaghan 2000;Camp and Tung 2007;Labitzke and Kunze 2009;Matthes et al 2010;Scaife et al 2013;Gray et al 2016;Rao andRen 2017, 2018;Rao et al 2019a), El Niño-Oscillation (ENSO) SST anomalies (Garfinkel and Hartmann 2007;Wei et al 2007;Bell et al 2009;Calvo et al 2009;Ineson and Scaife 2009;Weinberger et al 2019;Rao and Ren 2016;Rao et al 2019b), and atmospheric internal variation in the AMIP-type run; 3) lack of interactive chemistry module and ozone feedbacks (Silverman et al 2018;Naoe and Yoshida 2019); and 4) insufficient improvements of the nonorographic gravity wave parameterization (Rind et al 2014;Geller et al 2016;Naoe and Yoshida 2019). In contrast, some of the models participating in the seasonal to subseasonal (S2S) project appear to simulate a HT effect statistically indistinguishable from that observed (Garfinkel et al 2018c).…”
Section: Introductionmentioning
confidence: 99%